Aspectos econômicos da regência jurídica humanista em face das indústrias alimentícias como garantia à saúde dos obesos - Cruz, Ivelise Fonseca da (2012)
The vast growth of economic liberalism and is necessary to emphasize the man as the center of things, realizing their human dignity through the integral humanism. The incentive of love of neighbor and the exaltation of the fraternity, to compose the relationships and social laws result, then, the preservation and promotion of human health. The strengthening of the brotherhood of the thesis occurs when the clear identification of responsibility of the state, community, society, all in the preservation of fundamental human rights, encouraging the essentiality of the information, exercise and promote the right to food security, opportunity to promote awareness and increasing knowledge of the development of food products from the most diverse. Once the proper identification of obesity as a crop for human rights abuse, is with the literature review that this research aims to clarify the issues that compromise the full experience of human health. And finally, in a positive way, it was pointed out guiding paradigms that help as steps in human progress, in order to facilitate the search for the right to happiness for all in all, for everyone